Dysregulation of the cGAS-STING Pathway in Monogenic Autoinflammation and Lupus - Wobma, Holly; Shin, Daniel S.; Chou, Janet; Dedeoğlu, Fatma (Frontiers in Immunology, 2022)
One of the oldest mechanisms of immune defense against pathogens is through detection of foreign DNA. Since human DNA is compartmentalized into the nucleus, its presence in the cytosol heralds a potential threat. The cGAS-STING pathway is one of the most important cytosolic DNA sensing pathways and leads to interferon signaling, inflammasome activation, autophagy, and cell death. While STING signaling is protective at physiologic levels, chronic activation of this pathway can instead drive autoinflammation and autoimmunity. Here we discuss several monogenic disorders of the STING pathway that highlight its impact on both innate and adaptive immunity in the progressive loss of tolerance. The potential relevance of STING signaling in systemic lupus erythematosus is then discussed with a focus on future avenues for monitoring and targeting this pathway.